2021
DOI: 10.1177/21501327211018354
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Promoting Racial Diversity in Healthcare Settings to Address Disparities in Pandemic Crisis Management

Abstract: Background: Health disparities have become apparent since the beginning of the COVID-19 pandemic. When observing racial discrimination in healthcare, self-reported incidences, and perceptions among minority groups in the United States suggest that, the most socioeconomically underrepresented groups will suffer disproportionately in COVID-19 due to synergistic mechanisms. This study reports racially-stratified data regarding the experiences and impacts of different groups availing the healthcare system to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… 33 In addition, highly educated people may be more likely to have positive prior health care experiences positively impacting trust in health authorities, batter access to reliable health information sources, and better understand the perceived benefits of regular visits to the diabetes management program compared to the low educated people. 14 , 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 In addition, highly educated people may be more likely to have positive prior health care experiences positively impacting trust in health authorities, batter access to reliable health information sources, and better understand the perceived benefits of regular visits to the diabetes management program compared to the low educated people. 14 , 16 …”
Section: Discussionmentioning
confidence: 99%
“… 14 Moreover, cultural factors such as norms, beliefs, and trust play a critical role in the decision to use health care, and these factors tend to influence vulnerable groups strongly which may cause the low use of health care for this particular group. 15 , 16 In the context of Indonesia, studies have shown that poorer groups use health services less frequently than wealthier groups, even though all of these groups are covered by the NHI program. 17 This suggests the potential for inequalities in access to diabetes management programs among NHI beneficiaries with different backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among those with Arab ethnicity found significant differences in mortality on the use of anakinra (24% in the intervention vs. 67% in the control group, P = 0.013). The only RCT included in this meta-analysis was conducted in France, suggesting that the availability of racial and ethnically stratified data is scarce when it comes to the assessment of anakinra as a viable treatment option for COVID-19 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CORIMUNO trial found that the requirement for invasive mechanical ventilation was reduced among those treatments with anakinra (Odds ratio = 0.38, P = 0.02), and the mortality risk was also reduced in nonintubated patients (Odds ratio = 0.32, P < 0.001) [ 18 ]. The trial’s objectives were to assess the safety and efficacy of anakinra in nonhospitalized intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 The pandemic also revealed the need for a diverse and culturally competent HHR to cater to the requirements of marginalized communities. 21 Specific populations (e.g., ethnic minorities, Indigenous communities, and low-income people) were disproportionately impacted by the virus due to preexisting social determinants of health and systemic inequities. 19 Geography and the rural divide Canada's vast geography presents unique challenges for accessing healthcare, particularly in rural areas.…”
Section: Healthcare Equity and Related Challengesmentioning
confidence: 99%